Climate change mitigation and energy policy in development cooperation: what role for renewable energy technologies? - Imme Scholz; Matthias Krause (Deutsches Institut für Entwicklungspolitik (DIE), 2004)
Renewable energy technologies (RET) play an important role in industrialised countries' strategies for reducing CO2 emissions, and thus in mitigating climate change, as well as for achieving long-term energy security. Based on the principle of common but differentiated responsibilities, the North has an obligation to be a pioneer in this process. RET do not always have the same strategic importance in developing countries, since the latter are faced with other pressing development issues, and improvements in energy efficiency may entail major benefits for climate change mitigation. Development cooperation in the field of energy policy should thus be based on a broader strategy which includes both improvements in fossil fuel technologies and promotion of RET. A sustainable energy policy strategy has to consider partner country characteristics that affect the effectiveness and the desirability of policy instruments and overall responsibility for global climate change.Partner countries can be classified in three groups: Group I consists mainly of sub-Saharan African countries where energy poverty and unsustainable biomass use patterns prevail. Group II consists of countries in transition, where institutional problems often lead to low energy efficiency and high CO2 emissions. Group III consists of other developing countries and is dominated by dynamic economies with large populations and high and growing energy demand and CO2 emissions.Development cooperation in the field of energy should be based on three main strategies:A) The energy poverty and sustainable biomass management approach geared to country group I (also suitable for marginalized areas of country group III).B) The energy efficiency and energy market reform approach geared to country group II (complementary approach for group III).C) The climate change and energy security approach geared to country group III (also suitable for some countries of group II); this approach puts the strongest focus on RET promotion.
Keywords: 330; Energie; Deutsche + Europäische + multilaterale Entwicklungspolitik